Identifikasi genotipe jagung (Zea mays L.) toleran kekeringan berdasarkan karakter agronomi pada kondisi air optimum dan terbatas - Sartia Hama (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Corn (Zea mays L.) is a strategic food and feed commodity in Indonesia, but its productivity is still greatly influenced by water availability, especially on rainfed and dryland areas. Climate variability that increases the frequency and duration of drought has the potential to reduce corn growth, reproductive synchronization, and yield. This study aims to evaluate agronomic performance and identify drought-tolerant corn genotypes by comparing optimal and limited water conditions. The study was conducted at the Maros Agricultural Experiment Station, South Sulawesi, from March to June 2025, using a split-plot design with three replications. The main treatments consisted of optimal water conditions and moderate drought stress, while the subplots consisted of 10 candidate hybrids and 4 comparison varieties.The parameters observed included plant height, anthesis–silking interval (ASI), seed yield, yield per hectare, and drought stress sensitivity index (S). The results showed that drought stress reduced plant height and yield per hectare and widened the ASI value in several genotypes, but seed yield remained relatively stable between the two water conditions. Based on the drought stress sensitivity index, genotypes H12 (NK 33) and H8 were classified as tolerant, while other genotypes varied from moderately tolerant to sensitive. Thus, genotypes with relatively stable growth, low ASI, high yield, and low S value have the potential to be developed as candidates for drought-tolerant corn varieties for dry and rainfed lands.